The Influence of Entrepreneurial Orientation, Market Orientation, and Product Innovation on the Marketing Performance of Culinary MSMEs in Cirebon City - Fadel Muhamad; Zahwa Shofiyaturrahmah; Soesanty Maulany (Journal Research of Social Science, Economics, and Management, 2024)
This research was conducted with the aim to analyze the influence of entrepreneurial orientation, market orientation and product innovation on marketing performance in culinary MSMEs in Kesambi District. This research method uses quantitative research methods. The results showed that the first hypothesis was accepted, which means that entrepreneurial orientation has a positive and significant effect on the marketing performance of the Research. The results showed that the second hypothesis was accepted, which means that market orientation has a positive and significant effect on marketing performance. The results showed that the third hypothesis was accepted, which means that product innovation has a positive and significant effect on marketing performance. The results showed that the fourth hypothesis was accepted, which means that Entrepreneurial Orientation, Market Orientation and Product Innovation have a positive and significant effect simultaneously on marketing performance. Based on the results of the analysis that has been described regarding the influence of entrepreneurial orientation, market orientation and product innovation on the marketing performance of culinary MSMEs in the city of Cirebon, especially in Kesambi District, it is concluded that Entrepreneurial Orientation has a positive and significant effect on Marketing Performance. Market Orientation has a positive and significant effect on Marketing Performance. Product Innovation has a positive and significant effect on Marketing Performance. Entrepreneurial Orientation, Market Orientation and Product Innovation have a positive and significant effect simultaneously on marketing performance.